Invertebrate prey availability limits reproductive success but not breeding population size in suburban House Sparrows Passer domesticus. (23rd April 2015) - Peach, Will J.; Mallord, John W.; Ockendon, Nancy; Orsman, Chris J.; Haines, William G.
Abstract : Factors affecting avian demography and abundance in urban landscapes are poorly understood and this hinders attempts to manage urban bird communities. Several recent studies indicate that lack of invertebrate prey in urban landscapes may constrain avian productivity and fitness relative to that in other habitats. House Sparrow Passer domesticus populations have undergone large declines in many European urban centres and inadequate reproductive success linked to invertebrate availability has been postulated as a potential cause of these declines. We conducted a replicated supplementary feeding experiment to test whether the availability of invertebrate prey limits the breeding success and adult abundance (colony size) of House Sparrows in suburban London, where House Sparrow populations declined by 60% during the decade preceding our study. Daily mealworm provision over two successive breeding seasons, sufficient to provide 82% of chick energy requirements of House Sparrow pairs nesting within 50 m of feeders, had a large positive impact on the abundance of recently fledged birds (+62%), but only a small positive impact, limited mainly to small colonies, on the overall abundance of territorial males. Colony growth was only weakly related to fledgling abundance in the previous year and did not appear to be constrained by nest‐site availability. Conservation interventions that enhance invertebrate availability for suburban House Sparrows may increase reproductive success but are unlikely, on their own, to lead to population growth or recovery.